Clinical Practice Guidelines for Peritonitis Treatment. - Frank Carlos Alvarez Li; Carlos Jaime Geroy Gómez; Diosdania Alfonso Falcón; Alexis Díaz Mesa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Peritonitis Treatment. It is a general or local inflammatory process of the peritoneal membrane after a chemical irritation, bacterial invasion (intra-abdominal infection), local necrosis or direct contusion. It includes concept, classification, diagnosis, and medical and surgical treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.